CONSTITUTIONAL COURT OF SERBIA vs. CONSTITUTION – Doctrine of the substantive law-making authority - Simovic, Darko (COLLECTION OF PAPERS, FACULTY OF LAW NIŠ, 2025)
Serbia’a Constitution of 2006, besides numerous shortcomings in regulating a state of emergency, appears to offer improved solutions as it seeks to establish different guarantees against possible abuse of state of emergency. This is particularly noticeable when it comes to the distribution of powers in the state of emergency regime, as well as in the additional protection of human rights. Serbia's experience with the state of emergency in 2020 further pointed to the fact that the constitution, as a fundamental legal act, can never regulate the state of emergency in such a precise and detailed manner without certain open questions that will only be answered in practice. Before the Constitutional Court, questions were raised about the constitutionality of the decision on the declaration of the state of emergency, as well as the constitutionality of the measures taken to derogate human rights. The Court made two significant decisions but did not establish a consistent doctrine on a state of emergency. The challenges faced by Serbian society have confirmed the fact that there is a crisis of the Constitutional Court as the guardian of the constitution in Serbia. In such an environment, the Constitutional Court, viewed from the perspective of the rule of law principle, established an extremely dangerous doctrine of the "substantive" law-making authority. In order to be able to properly understand the scope of the Constitutional Court doctrine on the substantial law-making authority, the first part of the paper deals with the adoption of emergency measures based on the Constitution, while the second part provides a detailed analysis of the aforementioned doctrine.
Keywords: Constitution; constitutional court; state of emergency; rule of law; human rights; COVID-19